The European Union’s role in the world and the social dimension of globalisation - Tortell, L. (2007)
This discussion paper is based upon a multidisciplinary academic workshop held at DINÂMIA – Research Centre on Socio-Economic Change, Lisbon on 2-3 March that explored the nature of the external impact of the EU in relation to the social dimension of globalisation. In its widest sense, the social dimension of globalisation concerns the effects on people and societies of the globalisation of economic systems internationally. This workshop focussed largely on themes such as labour standards, decent work, employment, gender, health and human rights. In the current role as the holder of the EU Presidency, Portugal has an important role to play in relation to the EU’s external role; this document provides an overview to orient future actions. Given that the globalisation phenomenon is highly contested in public debate, focussing on its social dimension could provide a way in which to humanise globalisation and diffuse concern. It could, quite simply, legitimise the EU’s role in the world, particularly given the putative European social model, and the fact that the EU is a potentially powerful player in this context. EU initiatives in this area involve development, international relations, trade, governance and other policies, as well as indirect diffusion of social issues. Overall, the best approaches are those that combine different policies and both soft and hard approaches; that are coherent with internal EU policies; and in which social goals are consistent with trade and foreign policy goals. Geographical consistency is also necessary and, further, the role of the various actors should be clearly identified, both in terms of EU institutions and in relation to non-EU actors. Currently there are lacks in consistency and coherence, as well as doubts as to the EU’s commitment, ability and success in promoting the social dimension of globalisation. On the other hand, opportunities clearly exist, not least because the effects of globalisation are largely positive. This is an area in which further attention from both policy-makers and academics should be focussed, particularly in relation to the questions surrounding the success of programmes and policies, their coherence and consistency, the perspective of the developing world, and the involvement of civil society actors. Further, in practical terms, a periodic assessment report addressing the EU’s role in relation to the social dimension of globalisation and an international forum on the subject could usefully raise the profile of the EU’s external role in relation to the social dimension of globalisation and provide the first step in the next stage of this project.